PEMANFAATAN BAHAN LIMBAH SEBAGAI MEDIA PEMBELAJARAN IPA DI SEKOLAH DASAR: STUDI LITERATUR - Alfindi, Trisma; Edwita; Rahmi Darman, Dina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary school science learning often faces obstacles due to abstract concepts that are difficult for students in the concrete operational phase to comprehend, which is further exacerbated by the high cost of factory-made instructional media. This study aims to map out the effectiveness and typology of utilizing organic and inorganic waste materials as alternative learning media in elementary science education. The method employed is a Systematic Literature Review (SLR) by synthesized 29 accredited scientific articles published between 2021 and 2026 extracted from Google Scholar and DOAJ databases. The results indicate that recycling waste into science props offers multi-dimensional benefits. Economically, it provides a low-cost and independent solution to laboratory facility shortages. Pedagogically, concrete recycled media successfully reduces verbalism in teaching, enhances retention, and boosts students' cognitive comprehension. Furthermore, integrating waste into learning activities triggers an ecological impact by fostering environmental awareness and the 3R (Reduce, Reuse, Recycle) habits from an early age. Professionally, this approach enhances teachers' motor skills and creativity in designing sustainable school waste management. In conclusion, the optimization of waste materials functions effectively as a strategic, interactive, and sustainable media alternative for science instruction in elementary schools.